Oral health-related quality of life and standard of treatment in aggressive periodontitis patients more than 5 years after therapy - Bäumer, Amelie; Kappesz, Dieter; Ozga, Ann-Kathrin; Mertens, Christian; Eickholz, Peter; Pretzl, Bernadette (Journal of clinical periodontology, 2018)
Objectives: To assess OHRQoL in patients with aggressive periodontitis (AgP) after periodontal treatment using the Oral Health Impact Profile-49 (OHIP-49) and compare to patients’ dental status. Material and methods: More than 5 years after therapy, 71 patients were examined and answered the OHIP-questionnaire. The dental and periodontal status were assessed according to the SSO (Swiss Dental Society) criteria. Descriptive statistics were performed with SPSS, correlation analysis and tests for differences using R 3.2.2. Results: More than 90% of all patients showed no probing depths (PD) >5 mm, a bleeding on probing (BOP) index below 35%, and a sufficient function. Four patients showed no visible plaque, PDs ≤ 3 mm, a BOP below 10%, and an optimum function. Non-smoking and compliant patients exhibited a more favourable status. The OHIP-49 added up to 24.9 points, representing a comparatively high satisfaction of AgP-patients with their oral status. The subscale which most patients reported impairment in was “functional limitation.” A correlation between quality standard and the OHIP-49G could only be shown in the psychological disability subscale. Conclusion: After treatment, a moderate to high quality level can be retained over more than 5 years. Most patients are satisfied with their oral health. Correlations between the objective and subjective view could not be found, apart from the subscale “psychological disability.”